ІНСТИТУТИ ОПОДАТКУВАННЯ: ФОРМИ ПРОЯВУ ТА ЛОГІКА ФУНКЦІОНУВАННЯ - Сидорович, Олена Юріївна (Науковий журнал «Світ фінансів», 2017)
Сидорович О. Ю. Інститути оподаткування: форми прояву та логіка функціонування. Обґрунтовано, що в умовах сучасних соціально-економічних, суспільних і цивілізаційних трансформацій, існує гостра потреба пошуку відповідних теоретичних доктрин, здатних пояснити природу процесів, що мають місце в усіх сферах життя суспільства, зокрема в сфері оподаткування. На основі використання інституціонального підходу розглянуто сутність, закономірності розвитку та особливості функціонування одного з найбільш історично давніх суспільних інститутів держави – інституту оподаткування. Встановлено, що інституціональна сутність оподаткування може виявлятись у певних різновидах, як: норми, правила гри, стереотипи поведінки та основи трансакційного обміну. Запропоновано авторське бачення та трактування формального і неформального інститутів оподаткування. Сидорович Е. Ю. Институты налогообложения: формы проявления и логика функционирования. Обосновано, что в условиях современных социально-экономических, общественных и цивилизационных трансформаций, существует острая необходимость поиска соот- ветствующих теоретических доктрин, способных объяснить природу процессов, имеющих место во всех сферах жизни общества, в том числе в сфере налогообложения. На основе использования институционального подхода рассмотрены сущность, закономерности развития и особенности функционирования одного из самых исторически древних общественных институтов государства – института налогообложения. Установлено, что институциональная сущность налогообложения может проявляться в определенных разновидностях, как: нормы, правила игры, стереотипы поведения и основы трансакционного обмена. Предложено авторское видение и трактовка формального и неформального институтов налогообложения. Sydorovych O. Тах institutions: forms of displaying and logic of functioning. Introduction. Modern economic, social and civilization transformation that has gripped mankind in recent decades is characterized by a number of specific, deep and fundamental changes of social and economic systems of different levels, their extensive networks and hierarchies. There is an increasing dependence of national economies, spread and depth of the impact on social and economic processes that are beyond public authorities, increase of cultural, social and information communications. These processes allow to can explain and justify the nature of the processes taking place in all spheres of society. Purpose. The purpose of the paper is to find and develop theoretical and methodological approaches of development and functioning of a social institution – tax institution. Usage of institutional paradigm to the investigation of the taxation processes allows to integrate the multiplicative approaches from economics theory and other social sciences; to identify alternative areas of knowledge of this social phenomenon in the local, national and global fiscal space. Results. It was established, that taxation is one of the most historically ancient public institutions of the state, forms, types and mechanisms of which is an indicator of the evolution stage in the society. These forms vary in the process of social evolution and are affected by the relevant objective and subjective economic, ideological and political conditions. Determination of the institutional nature of taxation allows to consider their functioning in certain forms: as norms, rules, attitudes and behavior bases of transaction exchange. Furthermore, in the article author identifies the specific of functioning within two types of tax institutions: formal and informal, with highlighting the characteristics of their functioning and the features of the impact in terms of individuals, business and society. Conclusion. The nature of the tax institutions functioning is determined by various options of dialectical nature of formal and informal components, and their institutional interaction. Formal institutions are stated in laws and various written orders, which are obligatory for a particular area. The basic principles of their implementation are universality, publicity, reasonableness, transparency, clarity, and existence of coercion to implement them. This informal institutions, which are functioning as an analogue to formal units, have common and divergent features, they are “unwritten” rules implemented in the form of social arrangements and conventional restrictions. The author determines tax nature, its formal and informal components which allow to present their own interpretation. According to it, tax institutions are a complex of formal and informal norms, rules of behavior and restrictions and implementation mechanisms in order to ensure the realization and regulation of relations that deal with dispossession and aappropriation made by different government levels concerning taxpayers income for satisfying the interests of different social groups.